Distinct roles of the histone chaperones NAP1 and NRP and the chromatin‐remodeling factor INO80 in somatic homologous recombination in Arabidopsis thaliana. (8th September 2016) - Zhou, Wangbin; Gao, Juan; Ma, Jing; Cao, Lin; Zhang, Chi; Zhu, Yan; Dong, Aiwu; Shen, Wen‐Hui
Summary: Homologous recombination (HR) of nuclear DNA occurs within the context of a highly complex chromatin structure. Despite extensive studies of HR in diverse organisms, mechanisms regulating HR within the chromatin context remain poorly elucidated. Here we investigate the role and interplay of the histone chaperones NUCLEOSOME ASSEMBLY PROTEIN1 (NAP1) and NAP1‐RELATED PROTEIN (NRP) and the ATP‐dependent chromatin‐remodeling factor INOSITOL AUXOTROPHY80 (INO80) in regulating somatic HR in Arabidopsis thaliana . We show that simultaneous knockout of the four AtNAP1 genes and the two NRP genes in the sextuple mutant m123456‐1 barely affects normal plant growth and development. Interestingly, compared with the respective AtNAP1 ( m123‐1 and m1234‐1 ) or NRP ( m56‐1 ) loss‐of‐function mutants, the sextuple mutant m123456‐1 displays an enhanced plant hypersensitivity to UV or bleomycin treatments. Using HR reporter constructs, we show that AtNAP1 and NRP act in parallel to synergistically promote somatic HR. Distinctively, the AtINO80 loss‐of‐function mutation ( atino80‐5 ) is epistatic to m56‐1 in plant phenotype and telomere length but hypostatic to m56‐1 in HR determinacy. Further analyses show that expression of HR machinery genes and phosphorylation of H2A.X (γ‐H2A.X) are not impaired in the mutants. Collectively, our study indicates that NRP and AtNAP1 synergistically promote HR upstream of AtINO80‐mediated chromatin remodeling after the formation of γ‐H2A.X foci during DNA damage repair. Significance Statement: Homologous recombination occurs within the context of a highly complex chromatin structure, so disassembly and reassembly of nucleosomes is needed. Here we show that the H2A/H2B histone chaperones NRP1 and NRP2 act synergistically with the four AtNAP1 histone chaperones to promote somatic homologous recombination. These chaperones are epistatic to another chromatin‐remodeling factor, AtINO80, in both spontaneous and damage‐induced homologous recombination.